EMPTY FRUIT BUNCH COMPOST AND OIL PALM YIELD IMPROVEMENT: A SYSTEMATIC REVIEW OF AGRONOMIC PERFORMANCE AND SOIL HEALTH OUTCOMES - Hamdani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Empty Fruit Bunch (EFB) is a significant solid biomass residue produced by the palm oil industry, which could potentially be recycled as organic compost. More and more people are promoting the use of EFB compost to improve oil palm productivity, soil quality, and assist in sustainable plantation management. A systematic analysis was conducted to evaluate the impact of EFB compost on oil palm agronomic performance and soil health outcomes. An SLR was conducted in accordance with the PRISMA 2020 guidelines. Scopus, Web of Science, and ScienceDirect were used to identify articles published between 2021 and 2026 that met specific eligibility criteria. EFB compost has been found to have a positive impact on fresh fruit bunch yield, nutrient use efficiency, soil organic carbon, chemical exchange capacity, and microbial activity in the literature reviewed. Depending on the plantation age, compost maturity, application rate, soil type, and environmental conditions, the effectiveness of compost application can vary. The agronomic and environmental benefits are most consistent when EFB compost is integrated with inorganic fertilizers.